INTERAKSI SOSIAL ANTARA MAHASISWI PENGHUNI ASRAMA DI KELURAHAN SIMPANG BARU ( STUDI KONFLIK DI ASRAMA KARIMUN PUTRI DANG MELINI) - Hasikin, Nurul; ", Risdayati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Students who live in a dorm and who live with their relatives are different in terms of life style. It is known that students who live with their relatives are more capable in handling the everyday conflict which is faced. The conflict happened because of the daily interaction among the students and their relatives who they live with. In contrast, the students who live in a dorm which is known that there are variety of people with their own characteristics. The research metodhs using purposive sampling technique.Â  Most of them who are involved in the conflict will be thinking of moving on to another place which is far away from the old one. This research was conducted to the female students who live in Asrama Karimun Putri Dang Melini and get involved with their private conflict. This research is aimed to analyse the factors which causes the private conflict which is usually happened among the female students who live in Asrama Karimun Putri Dang Melini and to know the solution of it. The eight of the female students who Live in Asrama Karimun Putri Dang Melini were selected to be the sample of this research. In collecting the data the techniques which were used are observation, interview and documentation. The technique which was used in analysing the data was descriptive-qualitative that was by revealing the fact, the condition, the phenomena, the variable and the condition which was happened during the research and provide it just the way it is. Based on this research, it can be concluded that the factors which cause the private conflict in Asrama KArimun Putri Dang Melini are, 1) the difference of feeling and principle, 2) The difference of culture, 3) The difference of goal in life, 4) The change of social value and the way of overcoming it are, 1) Negotiation, 2) conciliation, 3) Meditation and 4) Arbitration. Â Keywords: Interaction, conflict, the solution of the conflict.